2022
DOI: 10.1039/d2nj00055e
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2Tx (MXene)-wrapped V2O5/Fe2O3 composites for enhanced-performance supercapacitors

Abstract: Among transition-metal-oxides, vanadium oxides and iron oxides have attracted much attention for electrochemical energy storage devices due to their high theoretical specific capacities and multiple variable valence states of V...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As shown in Figure S2, accordion-like layered MXene sheets were formed by etching MAX with a printed strut structure. , From Figure a, it could be observed that pure V 2 O 5 presented a massive structure due to the self-aggregation of V 2 O 5 nanoparticles . From Figure b–e, it was obvious that the self-aggregation of V 2 O 5 gradually weakened and a clear nanosheet structure appeared with increasing ratio of MXene/V 2 O 5 from 10 to 40 wt %, suggesting that V 2 O 5 nanoparticles were successfully loaded on the surface of MXene nanosheets .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure S2, accordion-like layered MXene sheets were formed by etching MAX with a printed strut structure. , From Figure a, it could be observed that pure V 2 O 5 presented a massive structure due to the self-aggregation of V 2 O 5 nanoparticles . From Figure b–e, it was obvious that the self-aggregation of V 2 O 5 gradually weakened and a clear nanosheet structure appeared with increasing ratio of MXene/V 2 O 5 from 10 to 40 wt %, suggesting that V 2 O 5 nanoparticles were successfully loaded on the surface of MXene nanosheets .…”
Section: Resultsmentioning
confidence: 90%
“…34,47 From Figure 3a, it could be observed that pure V 2 O 5 presented a massive structure due to the self-aggregation of V 2 O 5 nanoparticles. 48 From Figure 3b−e, it was obvious that the self-aggregation of V 2 O 5 gradually weakened and a clear nanosheet structure appeared with increasing ratio of MXene/V 2 O 5 from 10 to 40 wt %, suggesting that V 2 O 5 nanoparticles were successfully loaded on the surface of MXene nanosheets. 49 In particular, MXV-4 showed a special uniform porous structure, which indicated that V 2 O 5 nano-particles could grow uniformly on the surface of MXene when the mass ratio of MXene to V 2 O 5 was 4: 6.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Wang et al [ 295 ] reported the synthesis of Ti 3 C 2 T x -wrapped V 2 O 5 /Fe 2 O 3 (Ti 3 C 2 T x @VFO) nanostructures using a hydrothermal method. The VFO nanostructures on carbon cloth showed a capacitance of 435.2 mF cm −2 at 2 mA cm −2 .…”
Section: Ternary Mxene-based Composites For Supercapacitorsmentioning
confidence: 99%
“…[6][7][8] Recently, considering their abundance, low cost and excellent properties, transition metal oxides (TMOs) and transition metal sulfides (TMSs) have been studied as pseudocapacitor electrode materials for supercapacitors, e.g., FeS 2 , MoO 3 , Co 3 O 4 , CuS, Mn 3 O 4 , etc. [9][10][11][12][13] Owing to the redox reaction mechanism, these materials can express higher capacitance than electric double-layer capacitors (EDLCs). 14,15 Compared to transition metal oxides, transition metal sulfide electrodes show better electrical conductivity due to their lower band gap and electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%
“…, FeS 2 , MoO 3 , Co 3 O 4 , CuS, Mn 3 O 4 , etc. 9–13 Owing to the redox reaction mechanism, these materials can express higher capacitance than electric double-layer capacitors (EDLCs). 14,15 Compared to transition metal oxides, transition metal sulfide electrodes show better electrical conductivity due to their lower band gap and electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%